DECISION-MAKING MODEL FOR SELECTING GREEN BUILDING MATERIALS IN SUPPORTING MALAYSIAN SUSTAINABILITY - AL-ATESH, EZZADDIN ABDULLAH ALI (2021)
In recent years, the building industries' contribution is increasingly prominent to environmental issues such as CO2 and Greenhouse gas emissions.